2021
DOI: 10.1111/add.15366
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with severity, incidence or persistence of internet gaming disorder in children and adolescents: a 2‐year longitudinal study

Abstract: AimThis study examined factors associated with severity, incidence and/or persistence of internet gaming disorder (IGD) in children and adolescents. Design, Setting, Participants Prospective cohort study with 2-year follow-up study in South Korea. A total of 2319 3rd-, 4th-and 7th-graders enrolled into the internet user cohort for unbiased recognition of gaming disorder in early adolescence [internet user Cohort for Unbiased Recognition of gaming disorder in Early adolescence (iCURE)] and analyzed for the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 39 publications
1
37
1
1
Order By: Relevance
“…Probable PIU prevalence was also higher than reported in studies before the pandemic (3.2 -3.7% (Kuss et al, 2013a(Kuss et al, , 2013b). Prevalence of probable IGD among younger people (<30 years old) was 8.6% in the survey population, higher than reported in studies among children and adolescents (1.2 -7.5% (Jeong et al, 2020;Rehbein et al, 2015;Taechoyotin et al, 2020;Wartberg et al, 2020)) before the pandemic. It increased more than 1.8 times (from 7.7% to 13.8%) during the pandemic.…”
Section: Discussioncontrasting
confidence: 67%
“…Probable PIU prevalence was also higher than reported in studies before the pandemic (3.2 -3.7% (Kuss et al, 2013a(Kuss et al, , 2013b). Prevalence of probable IGD among younger people (<30 years old) was 8.6% in the survey population, higher than reported in studies among children and adolescents (1.2 -7.5% (Jeong et al, 2020;Rehbein et al, 2015;Taechoyotin et al, 2020;Wartberg et al, 2020)) before the pandemic. It increased more than 1.8 times (from 7.7% to 13.8%) during the pandemic.…”
Section: Discussioncontrasting
confidence: 67%
“…In this study, ADHD symptoms were significantly associated with IGD symptoms, which is consistent with the findings of previous studies conducted across different populations. 11 , 43 , 44 The comorbidity of ADHD and IGD points to a common biological mechanism. Previous magnetic resonance spectroscopy and imaging studies have found that ADHD and IGD patients were both characterized by decreased N-acetyl-aspartate levels within the frontal lobe, altered functional connectivity of the posterior cingulate cortex, and gray matter volume.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns have been raised about encouraging video gaming [27] as the time-consuming nature of playing VGs has been found to induce people, especially adolescents, to play games for an excessive amount of time [29]. Spending persistent and excessive time on playing VGs is a fundamental risk factor for the development of pathological behavioral symptoms [30][31][32][33], which have recently been discussed as a formal psychological disorder by both the American Psychiatric Association (APA) and the WHO. In 2013, the APA included Internet Gaming Disorder (IGD) in the fifth revision of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) [34].…”
Section: Introductionmentioning
confidence: 99%
“…We also expected that parental knowledge of their offspring’s life and the parents’ time dedicated to gaming would be negatively correlated [ 29 , 59 ]. Moreover, based on past studies [ 60 ], we posited that parental monitoring of their offspring’s video gaming habits would be negatively related to time spent by the offspring on VGs, which, in turn, would have a positive direct effect on GD symptoms [ 30 , 31 , 32 , 33 ]. We also hypothesized indirect effects from the parental variables to time spent by the juveniles on VGs.…”
Section: Introductionmentioning
confidence: 99%